Nature of the special trial in cases of violence against women and other members of the family group. - Saravia Quispe, José Yván (2017)
This article analyzes the evolution in understanding the nature of the special trial established in Law 30364 - Law to Prevent, Punish, and Eradicate ViolenceAgainst Women and Other Members of the Family Group, pointing out the doubts generated by the procedural loopholes of such law when it was promulgated and its subsequent interpretation when its regulations came into force, establishing its main characteristics so that it is better understood when applied by the justice officials.